2020
DOI: 10.1093/jas/skaa041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed removal on thermoregulation and intestinal morphology in pigs recovering from acute hyperthermia

Abstract: Feed consumption increases body temperature and may delay a return to euthermia and exacerbate intestinal injury following acute hyperthermia recovery in pigs. Therefore, the study objective was to evaluate the effects of feed removal on body temperature and intestinal morphology in pigs exposed to acute hyperthermia and then rapidly cooled. Twenty-four gilts (78.53 ± 5.46 kg) were exposed to thermoneutral (TN; n = 12 pigs; 21.21 ± 0.31 °C; 61.88 ± 6.93% RH) conditions for 6 h, or heat stress (HS; 38.51 ± 0.60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
5
2
Order By: Relevance
“…Therefore, the lack of body temperature differences may have been a result of an overall reduction in feed intake in HS + AF pigs that placed them on a similar nutritional plane to the HS + NF pigs and reduced the potential for feeding-induced differences in body temperature. Furthermore, the reasons why the results of the current study contradict previous reports [ 11 , 16 ] may be related to the cooling procedure used or the severity of the heat load imposed. In the previous studies [ 11 , 16 ], pigs were rapidly cooled by cold water dousing following a constant and severe HS.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Therefore, the lack of body temperature differences may have been a result of an overall reduction in feed intake in HS + AF pigs that placed them on a similar nutritional plane to the HS + NF pigs and reduced the potential for feeding-induced differences in body temperature. Furthermore, the reasons why the results of the current study contradict previous reports [ 11 , 16 ] may be related to the cooling procedure used or the severity of the heat load imposed. In the previous studies [ 11 , 16 ], pigs were rapidly cooled by cold water dousing following a constant and severe HS.…”
Section: Discussioncontrasting
confidence: 88%
“…Furthermore, the reasons why the results of the current study contradict previous reports [ 11 , 16 ] may be related to the cooling procedure used or the severity of the heat load imposed. In the previous studies [ 11 , 16 ], pigs were rapidly cooled by cold water dousing following a constant and severe HS. However, in the current study, pigs were exposed to cyclic HS to replicate a natural summer production environment and were not rapidly cooled.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Under such conditions, Pearce et al [ 80 ] observed increase in ileum MUC2 after 6 h of exposure to HS which can act as a protective barrier for the intestine and may combat the decrease in intestinal integrity. However, in another study, pigs exposed to HS for 3 h showed a reduction of goblet cells in the jejunum and ileum [ 85 ], and this was also observed even during the recovery period of 7 days after constant exposure to HS for 3 days [ 81 ]. This suggests that mucin glycoprotein (MUC2) production and activity can be reduced as this is produced by the goblet cells which can then potentially compromise intestinal function; that could lead to higher risk of infection caused by increased bacterial adhesion to the epithelium [ 85 , 88 ].…”
Section: Intestinal Integrity and Function Of Pigs Under Heat Stressmentioning
confidence: 99%